Global responsibility: An exploratory corpus assisted discourse analysis of the Rohingya crisis in online media - Roe, Jasper (Journal of Modern Languages, 2021)
This study conducts an exploratory corpus-assisted discourse analysis of the representation of the Rohingya minority group across online news media in the United Kingdom. The purpose of the study is to identify and interpret the discursive patterns employed in popular online news media when depicting the Rohingya minority and associated crises affecting the group in Myanmar and worldwide. Through the use of a combination of frequency, collocation, and concordance analysis, a synchronic study was undertaken using data collected from fifteen major online news media producers in the United Kingdom. The data was collected over a period from January 2017 – August 2020 through freely accessible digital archives. The research study found that particular discourses of security, internationalization, and power are commonly employed when reporting on the Rohingya, while equally a sympathetic viewpoint is often adopted which focuses specifically on global responsibility and failures of international society. The findings offer insight into socio-political processes of representation and discourse in the ‘new social location’ (Scholz, 2019) of online news media, while offering relevant insight into the discourses of urgent and pressing humanitarian issues.